Силовое взаимодействие между близко расположенными проводящими микровключениями в диэлектрической среде во внешнем электрическом поле - Щерба, М.А. (Технічна електродинаміка, 2012)
The electrical forces arising between two closely located conducting micro-inclusions in an external electric field are studied. It is proved that the interaction of charges with opposite polarity on closely located convex surfaces of different conducting inclusions results in increasing of concentration of surface charges near the most closely located points of such surfaces. In this connection the electric field in the dielectric gap between these surfaces and the interaction between the inclusions are amplified. Moreover, despite of equality to zero total charge of each inclusion, the resultant force directed towards the second inclusion will act on it and this force will be increased according to the law-power function with decreasing distance between the inclusions.